Ответ:
1) ( х,у ) = ( 4,7 )
2) ( х,у) = ( 3,2 )
3) ( x,y ) = ( -1,3 )
4) ( х,y ) = ( 2,5 )
Объяснение:
1)
11-y-y=-3
y=7
x=11-7
x=4
(x,y ) = ( 4,7 )
2)
2(1+y)+3y+12
y+2
x=1+2
x+3
(x,y) = ( 3,2 )
3) -3x-2x=5
x=-1
y= -3 * ( -1 )
y= 3
( x , у ) = ( 1,3 )
4)
2x-(7-x) = -1
x=2
y=7-2
y=5
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
1) ( х,у ) = ( 4,7 )
2) ( х,у) = ( 3,2 )
3) ( x,y ) = ( -1,3 )
4) ( х,y ) = ( 2,5 )
Объяснение:
1)![\left \{ {{x-y=-3 } \atop {x=11-y}} \right. \left \{ {{x-y=-3 } \atop {x=11-y}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7Bx-y%3D-3%20%7D%20%5Catop%20%7Bx%3D11-y%7D%7D%20%5Cright.)
11-y-y=-3
y=7
x=11-7
x=4
(x,y ) = ( 4,7 )
2)![\left \{ {{2x+3y=12} \atop {x=1+y}} \right. \left \{ {{2x+3y=12} \atop {x=1+y}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7B2x%2B3y%3D12%7D%20%5Catop%20%7Bx%3D1%2By%7D%7D%20%5Cright.)
2(1+y)+3y+12
y+2
x=1+2
x+3
(x,y) = ( 3,2 )
3) -3x-2x=5
x=-1
y= -3 * ( -1 )
y= 3
( x , у ) = ( 1,3 )
4)![\left \{ {{2x-y = -1 } \atop {y=7-x}} \right. \left \{ {{2x-y = -1 } \atop {y=7-x}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7B2x-y%20%3D%20-1%20%7D%20%5Catop%20%7By%3D7-x%7D%7D%20%5Cright.)
2x-(7-x) = -1
x=2
y=7-2
y=5